Audit committee characteristics and bank performance: evidence from India. Issue 6 (4th August 2021) - Gupta, Neeraj; Mahakud, Jitendra
Abstract : Purpose: This study aims to investigate the impact of various audit committee (AC) characteristics on the performance of Indian commercial banks. Additionally, it also analyses the non-linear relationship of AC size and AC chairman tenure with bank performance. Design/methodology/approach: A panel data approach has been used in this study. The authors have used the fixed-effect estimation technique to examine the relationship between AC characteristics and bank performance during the period 2009–2010 to 2016–2017. Findings: The authors find that the professional financial education of the AC chairman and members positively affects bank performance. the frequency of the AC meetings and audit chair busyness bears an inverse relationship with performance. The findings are more or less consistent across the various bank performance measures and subsamples classified based on the time period and ownership of the banks. Practical implications: This study provides insights to policy regulators and policymakers who are entrusted with the establishment of ACs in the banks in light of the ongoing regulatory reforms. Originality/value: The study is among one of the early studies, which study the relationship between AC characteristics and bank performance in the light of recent regulatory reforms. It also extends the existing study by considering both public and private banks operating in India.